Chlorella-supplemented diet improves the health of honey bee (Apis mellifera) - Jang, Hyeonjeong; Ghosh, Sampat; Sun, Sukjun; Cheon, Kang Jun; Mohamadzade Namin, Saeed; Jung, Chuleui (Frontiers in Ecology and Evolution, 2022)
Nutritional stress is one of the major factors affecting honey bee health. Supplementing the pollen patty with microalgae enhances the protein content of the patty and therefore, is supposed to improve bee health. The objective of the present study was to investigate the effect of Chlorella as a dietary supplement on honey bee (Apis mellifera) health and physiology. We formulated honey bee feed by supplemented Chlorella, obtained commercially, with commercially available rapeseed pollen patty in different amounts i.e. 0.5, 2, 5, and 10%, and the treatment groups were recognized as P0.5, P2, P5, and P10 respectively. Pollen patty was set as a positive control and only 50% sucrose solution (no protein) as a negative control. Diets were supplied ad libitum to newly emerged workers in cages and observed food consumption patterns, longevity, and physiology including the development of muscle (brain, thorax, fat body), and glands (hypopharyngeal and acid), gene expression of nutrition-related gene vitellogenin of honey bee at different point of time of their age. Addition of Chlorella significantly increased food consumption pattern, longevity, gland development, muscle formation, and vitellogenin gene expression significantly in comparison to the only pollen or sugar diet. However, the response varied depending on the level of Chlorella supplementation. As depicted in most of the cases, P2 i.e. pollen diet with 2% of Chlorella supplement exhibited the best outcome in terms of all the tested parameters. Therefore, based on the results obtained in the present study, we concluded that 2% Chlorella supplementation to pollen patty could enhance the health of honey bees which in turn improves their performance of them.